2021
DOI: 10.1080/13546783.2021.1934899
|View full text |Cite
|
Sign up to set email alerts
|

Limits of the foreign language effect: intertemporal choice

Abstract: Intertemporal choice requires one to decide between smaller sooner and larger later payoffs and is captured by discount rates. Across two preregistered experiments testing three language pairs (Experiment 1) and with incentivized participants (Experiment 2), we found no evidence that using a foreign language benefited intertemporal choices. On the contrary, there was some evidence of stronger discounting when a foreign language was used. Our results confirm that more reflective individuals tend to discount les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…Experiment 1A. -Data for Experiments 1A and 1B come from Białek et al, (2022). N = 240 participants responded to discounting items presented in four blocks: accelerating gains, delaying gains, accelerating losses, and delaying losses.…”
Section: Additional Details Of the Experimentsmentioning
confidence: 99%
“…Experiment 1A. -Data for Experiments 1A and 1B come from Białek et al, (2022). N = 240 participants responded to discounting items presented in four blocks: accelerating gains, delaying gains, accelerating losses, and delaying losses.…”
Section: Additional Details Of the Experimentsmentioning
confidence: 99%
“…However, whether this is the case remains unclear. To the best of our knowledge, the only related study did not support such a prediction (Białek, Domurat, Paruzel-Czachura, & Muda, 2021). Instead, they found that participants speaking a second language did not change or even slightly increase their temporal discount rate.…”
Section: The Fle and Intertemporal Decision-makingmentioning
confidence: 63%
“…Białek et al (2021) report a marginally significant (p = .077) interaction between second language and cognitive reflection on the decision consistency. Although the FLE may not impact cognitive reflection (Białek et al, 2021;Costa, Foucart, Arnon, et al, 2014), Białek et al (2021) suggest that using a second language may disable the ability to use cognitive reflection to guide intertemporal decision.…”
Section: The Fle and Intertemporal Decision-makingmentioning
confidence: 91%
“…For example, the performance in various heuristic-and-biases tasks was unaffected by the language used (Maekelae & Pfuhl, 2019;Vives et al, 2018). Some negative effects of using a foreign language were also reported, such as decreased accuracy in logical reasoning (Białek et al, 2020), increased impatience (Białek et al, 2022), and difficulty in distinguishing between true and fake news (Muda et al, 2023).…”
Section: The Foreign Language Effectsmentioning
confidence: 99%